Sepsis Induced Acute Kidney Injury: Clinical Profile, Risk Factors and Outcomes in Tertiary Referral Centre - R, Sunil; fakruddin, Mohammad; Sandeep, R; C, Amogh; DM, Nutan kumar (International Journal of Innovative Research in Medical Science, 2017)
Sepsis increases the risk of development of acute kidney injury (AKI) and is associated with significant patient morbidity and mortality. Sepsis induced AKI is characterized by a distinct pathophysiology and therefore requires a different approach and management. A prospective study was conducted to look for pattern of sepsis induced AKI in South Indian population. A total of 234 patients were enrolled in the study .Patient’s detailed history, clinical examination and laboratory investigations were noted and source of sepsis was evaluated, patients were followed up till discharge or death. During follow up development of complications or requirement of renal replacement therapy was noted. Sepsis associated AKI was associated with significant morbidity and mortality.